2016
DOI: 10.1038/nmicrobiol.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

Host SHP1 phosphatase antagonizes Helicobacter pylori CagA and can be downregulated by Epstein–Barr virus

Abstract: Most if not all gastric cancers are associated with chronic infection of the stomach mucosa with Helicobacter pylori cagA-positive strains(1-4). Approximately 10% of gastric cancers also harbour Epstein-Barr virus (EBV) in the cancer cells(5,6). Following delivery into gastric epithelial cells via type IV secretion(7,8), the cagA-encoded CagA protein undergoes tyrosine phosphorylation on the Glu-Pro-Ile-Tyr-Ala (EPIYA) motifs initially by Src family kinases (SFKs) and then by c-Abl(9,10). Tyrosine-phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 48 publications
1
86
0
Order By: Relevance
“…Both pathogens share similar patterns of cell signaling pathways leading to proliferation, increased cell survival, immune evasion. Recent paper by Saju et al [9] showed that host's SHP1 phosphatase antagonizes Helicobacter pylori CagA and can be down regulated by EpsteinBarr virus. In vitro infection of gastric epithelial cells with EBV induces SHP1 promoter hypermethylation, which strengthens phosphorylation-dependent CagA action via epigenetic down regulation of SHP1 expression [9].…”
Section: Hsv1/2 and H Pylorimentioning
confidence: 99%
See 1 more Smart Citation
“…Both pathogens share similar patterns of cell signaling pathways leading to proliferation, increased cell survival, immune evasion. Recent paper by Saju et al [9] showed that host's SHP1 phosphatase antagonizes Helicobacter pylori CagA and can be down regulated by EpsteinBarr virus. In vitro infection of gastric epithelial cells with EBV induces SHP1 promoter hypermethylation, which strengthens phosphorylation-dependent CagA action via epigenetic down regulation of SHP1 expression [9].…”
Section: Hsv1/2 and H Pylorimentioning
confidence: 99%
“…Recent paper by Saju et al [9] showed that host's SHP1 phosphatase antagonizes Helicobacter pylori CagA and can be down regulated by EpsteinBarr virus. In vitro infection of gastric epithelial cells with EBV induces SHP1 promoter hypermethylation, which strengthens phosphorylation-dependent CagA action via epigenetic down regulation of SHP1 expression [9]. While H. pylori cause epigenetic silencing of tumour-suppressor genes to deregulate cellular pathways, EBV-positive tumors exhibit a widespread and distinctive DNA hypermethylation profile [10].…”
Section: Hsv1/2 and H Pylorimentioning
confidence: 99%
“…In addition to H. pylori , EBV, a ubiquitous human herpes virus with oncogenic potential, is associated with the development of gastric adenocarcinoma, and has been linked to ~9% of gastric cancer cases worldwide 6 . An exciting new study by Saju et al 7 now describes a paradigm of how a bacterium and a virus collaborate to potentially exacerbate a disease they can each cause independently.…”
mentioning
confidence: 99%
“…Specifically, Saju et al 7 report that a host phosphatase, SHP1 (also known as tyrosine-protein phosphatase non-receptor type 6 or PTPN6), interacts with H. pylori -delivered CagA and functions as a negative regulator of CagA phosphorylation. Using a combination of transient CagA transfections and co-culture of viable H. pylori cag + strains with gastric epithelial cells, the researchers demonstrate that CagA forms a complex with SHP1, which was independent of CagA tyrosine phosphorylation status and did not involve CagA EPIYA phosphorylation motifs 7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation